2010
DOI: 10.1108/14626001011088769
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of education for potential entrepreneurs: an international investigation

Abstract: PurposePreparing today's students for success and eventual leadership in the new global marketplace is one of the most important responsibilities in education today. This study seeks to represent the first, in‐depth analysis of future entrepreneurs and to show that its results indicate that the investment in entrepreneurship education is valuable.Design/methodology/approachA primary survey was conducted among first‐year Business Studies students from Australia, Portugal, Finland, Germany, Slovenia, Poland, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 17 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…The finding of this work confirmed that entrepreneurial education can determine students' mindset related to entrepreneurship. The result of this work reinforces preliminary findings of Sowmya et al (2010); Akmaliah et al (2016), Ridley et al (2017), andWardana et al (2020), which demonstrated this relation relationship. An underlying reason for this result is that the pedagogical approach in education has a positive impact on students' cognitive ability to register in the proposed activities in class and has created a favorable atmosphere for learning, with students playing an active role in gaining experience from their activities.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of this work confirmed that entrepreneurial education can determine students' mindset related to entrepreneurship. The result of this work reinforces preliminary findings of Sowmya et al (2010); Akmaliah et al (2016), Ridley et al (2017), andWardana et al (2020), which demonstrated this relation relationship. An underlying reason for this result is that the pedagogical approach in education has a positive impact on students' cognitive ability to register in the proposed activities in class and has created a favorable atmosphere for learning, with students playing an active role in gaining experience from their activities.…”
Section: Discussionsupporting
confidence: 91%
“…Gallant et al (2010) investigated the attitudes of students in Dubai towards entrepreneurship and their opinions about the role that Universities could play in fostering their interest towards entrepreneurship. In one of our previous studies (Varadarajan et al, 2010), the young female students in UAE showed more positive attitude and motivation towards entrepreneurship than their counterparts across the globe. Ryan et al (2011) found that motivation was an important factor in explaining the entrepreneurial success, especially among Emirati women.…”
Section: Entrepreneurship In the Uaementioning
confidence: 73%
“…Students' attitudes to entrepreneurship can be developed, based on their opinions to education (Harris and Gibson, 2008;Souitaris et al, 2007). In order to enrich policy in entrepreneurship education, researchers investigating the attitudes and motivation of female students towards entrepreneurship revealed that clear goals should be set for entrepreneurship education (Sowmya et al, 2010). Thus, we defined perceived positive attitudes towards entrepreneurship education as the perception on entrepreneurship training and courses during the COVID-19 pandemic.…”
Section: Literature Review and Hypotheses Development Perceived Positive Attitudes Towards Entrepreneurship Educationmentioning
confidence: 99%